Studies on the Growth Performance and Developnment of the Underground Parts (Tubers) of some Species of Dioscorea Linn. under Poona Climate - Singh, N. P. (Indian Forester, 1982)
In view of the various economic uses and medicinal properties attributed to the genus Dioscorea Linn., studies on the growth performance and development of the underground part. (tubers) of six species viz. Dioscorea alata Linn, D. bulbifera Linn D. esculenta Burk., D. hispida Dennst D. oppositifolia Linn. And D. penlaphylla Linn. And a variety viz D. penlaphylla Linn. Var. linnaei Ptain and Burk. Were undertaken under Poona climate and the same are presented below. In fact much data is available on such studies, though under different climatic conditions vide Wealth of India III: 67-75,1952. Climatic factors of the aroa for the experimental period are presented briefly. The studies reveoled that the seeds are not a good source for such studies; bulbils gave better results but, howevewer, tubers proved to he the only best ones. The duration of the aerial portion varied from 7-10 months in the various species. The weight of the tubers varied specieswise as also individually.